Photographic literacy : cameras in the hands of Russian authors - Reischl, Katherine M. H. (Ithaca [New York] : Cornell University Press, 2018)
"A primer in photographic literacy, focused on the sites of contact between photography and literary writing over roughly seventy years, this book traces the visual consciousness of modern Russian literature in the twentieth century as captured through the lens of the Russian author-photographer"--
Introduction : chasing Pushkin's photograph -- Tolstoy in the age of his technological reproducibility -- The diffusion of domesticated photography : Leonid Andreev, Vasily Rozanov, and Maximillian Voloshin -- Micro-geography, macro-world : Mikhail Prishvin -- Look left, young man! The international exchange of photo-narratives -- Conclusion : Nabokov, Solzhenitsyn, and the anxiety of photographic authorship.
"This publication is made possible in part from the Barr Ferree Foundation Fund for Publications, Department of Art and Archaeology, Princeton University."
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 06, 2018).
In English.
eBooks on EBSCOhost
Keywords: Literature and photography -- Russia -- History -- 20th century; Literature and photography -- Soviet Union -- History; Russian literature -- 20th century -- History and criticism; Photography in literature; Littérature et photographie -- Russie -- Histoire -- 20e siècle.; Littérature et photographie -- URSS -- Histoire; Littérature russe -- 20e siècle -- Histoire et critique; Photographie dans la littérature.; LITERARY CRITICISM -- Russian & Former Soviet Union; ART -- Russian & Former Soviet Union; Literature and photography; Photography in literature; Russian literature; Russia; Soviet Union; 1900-1999; Criticism, interpretation, etc; History